Maternal Stressful Life Events During the Periconceptional Period and Orofacial Clefts: A Systematic Review and Meta-Analysis. (October 2022) - Tran, Christina; Crawford, Andrew A.; Hamilton, Alexander; French, Clare E.; Wren, Yvonne; Sandy, Jonathan; Sharp, Gemma
Objective: To assess whether women who experience stressful life events during the periconceptional period are at higher risk of giving birth to a baby with an orofacial cleft (OFC). Design: Systematic review and meta-analysis of studies reporting the proportion of babies born with OFC to mothers exposed and unexposed to population-level or personal-level stressful life events during the periconceptional period. Six electronic databases were searched from inception to August 2020. Risk of bias was assessed using the Newcastle-Ottawa scale. Odds ratios (ORs) for the odds of OFC in babies of exposed mothers relative to unexposed controls were extracted and/or calculated. Random effects meta-analysis was undertaken, stratified by cleft subtype. Results: Of 12 eligible studies, 8 examined experience of personal events and 4 examined population-level events. Studies demonstrated low-moderate risk of bias and there was indication of publication bias. There was some evidence that personal stressful life events were associated with greater odds of cleft lip and/or palate (six studies, OR 1.63, 95% confidence interval (CI) 1.16, 2.30, P = 0.001) and cleft palate only (six studies, OR 1.45, 95% CI 1.02, 2.06, P = 0.04). Population-level events were associated with higher odds of OFC in studies that did not specify subtype (three studies, OR 1.64, 95% CI 1.19, 2.25, P = 0.002), but subtype stratified analyses were underpowered. Heterogeneity was high. Conclusions: Limited evidence indicated a weak positive association between maternal stressful life events during the periconceptional period and risk of OFC in the offspring, but further studies with greater consistency in research design are needed.